The photoprotective and collagen stimulatory effects of labisia pumila var pumila extract on UVB irradiated human skin fibroblast (HSF1184) cells - Mohd. Mukrish Mohd. Hanafi @ Hanafiah, 1985-; Mohamad Roji Sarmidi, supervisor; Fadzilah Adibah Abdul Majid, supervisor; Fakulti Kejuruteraan Kimia (2012)
Thesis (Sarjana Kejuruteraan (Bioproses)) - Universiti Teknologi Malaysia, 2012